2021
DOI: 10.3389/fsurg.2021.648779
|View full text |Cite
|
Sign up to set email alerts
|

The Myth of Median Nerve in Forearm and Its Role in Double Crush Syndrome: A Cadaveric Study

Abstract: Purpose: This study aims to histologically compare the median nerve in the arm, forearm, and wrist, to help understand how cervical radiculopathy in a double crush phenomenon causes distal nerve dysfunction at the carpal tunnel and median nerve with concurrent absence of symptoms at the forearm.Methods: The study was performed on 12 fresh cadaveric upper limbs free from any injury or operation. Male cadavers in the age range of 35–40 years were used. The dissection of the median nerve and the histological exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a study by Sunderland and Bradley [10], the authors reported greater thickness of the perineurium at the wrist than at the axilla for the ulnar and median nerves. In contrast, in a study by Abdalbary et al [15], greater perineurium thickness was observed in the forearm compared to the arm and wrist.…”
Section: Introductionmentioning
confidence: 61%
“…In a study by Sunderland and Bradley [10], the authors reported greater thickness of the perineurium at the wrist than at the axilla for the ulnar and median nerves. In contrast, in a study by Abdalbary et al [15], greater perineurium thickness was observed in the forearm compared to the arm and wrist.…”
Section: Introductionmentioning
confidence: 61%
“…We describe it more inclusively as median nerve compression in the forearm (MNCF) ( Figure 2 ) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. CTS is also well known to be associated with radiculopathy in the cervical spine due to a double crush phenomenon [ 24 , 25 , 26 , 27 ]. Failure to recognize a secondary site of compression can lead to incomplete resolution of symptoms.…”
Section: Etiology Of Failed Carpal Tunnel Releasementioning
confidence: 99%
“…Throughout the arm, the MN passes through many narrow structures where it may compress the nerve ( Abdalbary, Abdel-Wahed et al, 2021 ). The carpal tunnel is the most common location for MN entrapment ( Knutsen and Calfee, 2013 ; Kantarci, Ustabasioglu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%